Percepción de riesgo de contagio del COVID-19 en personal de salud - Perez Mogrovejo, Fiorella (2024)
The aim of this study was to analyze the perceived risk of COVID-19 infection among health personnel in Lima and Callao. We followed a qualitative approach with a reflexive thematic analysis design. Fifteen participants were interviewed. It was found that the perception of the risk of infection revolved around previous knowledge, the emotional state went from fear to calm. Likewise, the perception was affected by the sociocultural influence of the work environment, institutional, relational, beliefs and service vocation; as well as by personal experiences, which include risk situations and negative emotional charge. It is concluded that the perception of risk is centered on knowledge and emotions, related to social, cultural, and individual aspects.